Effect of fatigue on strength performance - Monteiro, L.; Masucca, L.; Garcia, J. M.; Carratala, V.; Calvo Rico, B. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
This study aim to determine the effect of fatigue on arm extensor muscles upon power, velocity, strength and rate of force development (RFD) output levels, throughout a simulate contest in judo athletes. Sixty-three male judo athletes of five national teams participated in this study, and were classified in two performance groups (elite, n=30; sub-elite, n=33). All participants performed an intermittent judo test - the COPTEST (a 5 minutes duration test, with 9 Nage-komis, 9 Uchi-komis, 9 Juji-gatame and 4 repetitions of Bench-press (BP) with the power-load in each minute, i.e., T1 to T5). BP load was the previous calculated power-loadings of the arm extensor muscles, and 3 measures were collected: (1) power, (2) velocity, and (3) RFD. Power-load (~50%1RM) was tested on a free-weights BP exercise, and an Isocontrol . Dynamic 5.1 Software was used to collect data. Standard statistical methods, one-way analyses of variance (ANOVA), and the repeated measures analysis of variance (between T1-T2 till T5) were used. The level of significance was set at 0.05. Significant differences were observed between: (1) performance groups in power, strength and RFD; (2) evaluations (T1 to T5) in power, velocity, and RFD. Moreover, the effect of fatigue on power, strength, velocity, and RFD (all, p=NS) is independent of performance group. Results showed that elite athletes were powerfull (+69 W to 200 W), stronger (+69 N to 184 N) and have superior explosive muscle strength (+15778 N.s-1 to 32648 N.s-1). In accordance, the maximization of the power development capacity must be a key component of judo training programs. Nevertheless, during the contest, the observed slight reduction in power and velocity (in both, elite and sub-elite groups) musts be investigated (i.e., changes in the contractile apparatus vs reduced muscle activation).